1988
DOI: 10.1002/prsb.720070415
|View full text |Cite
|
Sign up to set email alerts
|

Stability of acrylic monomers

Abstract: Certain procedures and tests have been developed to ensure that monomer products are sufficiently stable for manufacturing and handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It was found that PIT increases exponentially with decreasing the temperature. Thus, an Arrhenius-like relationship is found by plotting the logarithm of PIT against the inverse of absolute temperature (1/K). , As shown in Figure , a linear relationship between the logarithms of PIT from the isothermal calorimetric data and the inverse of temperature, Table , was obtained and the fitting parameters are given in eq . with PIT in min.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was found that PIT increases exponentially with decreasing the temperature. Thus, an Arrhenius-like relationship is found by plotting the logarithm of PIT against the inverse of absolute temperature (1/K). , As shown in Figure , a linear relationship between the logarithms of PIT from the isothermal calorimetric data and the inverse of temperature, Table , was obtained and the fitting parameters are given in eq . with PIT in min.…”
Section: Resultsmentioning
confidence: 92%
“…It is well-known that spontaneous polymerization is a safety concern during transportation of polymerizing substances. Large quantities of monomers are transported worldwide by railcars, ships, and trucks, which are not designed to mitigate the hazards of a runaway polymerization. Inhibitors are widely used to prevent the polymerization from occurring during transportation and storage. , Inhibitors can stabilize monomers for some period of time (polymerization induction time, PIT) until either oxygen or inhibitors have been depleted, after which the polymerization reaction proceeds at its normal rate.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylates are highly reactive compounds typically shipped with phenolic inhibitor compounds, such as p-methoxyphenol, to prevent uncontrolled polymerization reactions (i.e., from dissolved oxygen-based radicals, or UV light, or heat) from occurring (Kirch et al, 1988). Additionally, increased temperature increases the rate at which any polymerization occurs (Kirch et al, 1988). PGD macromonomers, as purified, lack free radical quenchers or added inhibitors, allowing several spontaneous polymerization possibilities in the absence of added free radical initiators.…”
Section: Polymerization Of Peg Glycolide Dimethacrylate (Pgd)mentioning
confidence: 98%
“…These results suggest that polymerization was initiated by endogenous free radicals despite absence of added initiator. Acrylates are highly reactive compounds typically shipped with phenolic inhibitor compounds, such as p-methoxyphenol, to prevent uncontrolled polymerization reactions (i.e., from dissolved oxygen-based radicals, or UV light, or heat) from occurring (Kirch et al, 1988). Additionally, increased temperature increases the rate at which any polymerization occurs (Kirch et al, 1988).…”
Section: Polymerization Of Peg Glycolide Dimethacrylate (Pgd)mentioning
confidence: 99%
“…It is noted that acrylic acid can experience violent polymerization. Thermally initiated, the monomer reacts energetically above about 115"C, despite the use of proper inhibitors [9]. Reaction rates corresponding to -2OO"CI min have been observed, suggesting that relief venting in case of pressure buildup becomes impractical.…”
Section: October 1989 181mentioning
confidence: 99%